2021
DOI: 10.1371/journal.ppat.1009824
|View full text |Cite|
|
Sign up to set email alerts
|

pUL21 is a viral phosphatase adaptor that promotes herpes simplex virus replication and spread

Abstract: The herpes simplex virus (HSV)-1 protein pUL21 is essential for efficient virus replication and dissemination. While pUL21 has been shown to promote multiple steps of virus assembly and spread, the molecular basis of its function remained unclear. Here we identify that pUL21 is a virus-encoded adaptor of protein phosphatase 1 (PP1). pUL21 directs the dephosphorylation of cellular and virus proteins, including components of the viral nuclear egress complex, and we define a conserved non-canonical linear motif i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(82 citation statements)
references
References 107 publications
(162 reference statements)
13
69
0
Order By: Relevance
“…Consistent with this hypothesis, the abundance alkyne-SM as a fraction of total alkyne-Cer plus alkyne-SM was higher in HaCaT21 versus HaCaT cells at early time points (0-30 min) during the chase (Fig pUL21 has multiple functions during infection, promoting the PP1-mediated dephosphorylation of not just CERT but of multiple different cellular and viral proteins [18]. It was therefore essential to identify a point mutant of pUL21 with impaired binding to CERT, but not to other cellular or viral partners, to dissect the functional significance of increased CERT activity during infection.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Consistent with this hypothesis, the abundance alkyne-SM as a fraction of total alkyne-Cer plus alkyne-SM was higher in HaCaT21 versus HaCaT cells at early time points (0-30 min) during the chase (Fig pUL21 has multiple functions during infection, promoting the PP1-mediated dephosphorylation of not just CERT but of multiple different cellular and viral proteins [18]. It was therefore essential to identify a point mutant of pUL21 with impaired binding to CERT, but not to other cellular or viral partners, to dissect the functional significance of increased CERT activity during infection.…”
Section: Resultssupporting
confidence: 57%
“…It was therefore essential to identify a point mutant of pUL21 with impaired binding to CERT, but not to other cellular or viral partners, to dissect the functional significance of increased CERT activity during infection. Defining the interaction surfaces of transient protein complexes presents a considerable challenge [45], made more difficult in the case of pUL21 and CERT by their containing multiple domains and regions of intrinsic disorder [18].…”
Section: Resultsmentioning
confidence: 99%
“…An alternative explanation for the hyperphosphorylation of pUs3, pUL31 and pUL34 in ΔUL21 infected cells is that pUL21 may promote their dephosphorylation ( Fig 9B ). This idea is strongly supported by a recent study from Graham and co-workers that demonstrated HSV-1 pUL21 is an adaptor protein for protein phosphatase 1 (PP1) and furthermore that pUL21 has a penchant for delivery of PP1 to pUs3 substrates to mediate their dephosphorlyation [ 36 ]. The fact that pUL21 and pUs3 are only found in members of the Alphaherpesvirinae raises the intriguing possibility that pUL21 exists, in part, to specifically counter the activities of pUs3.…”
Section: Discussionmentioning
confidence: 91%
“…HSV-2 pUL21 regulates the phosphorylation status of the NEC dephosphorlyation [36]. The fact that pUL21 and pUs3 are only found in members of the Alphaherpesvirinae raises the intriguing possibility that pUL21 exists, in part, to specifically counter the activities of pUs3.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…These genes are essential for the viral life cycle in vivo, and many of them play roles in viral assembly and egress. Some of these conserved assembly proteins participate in self-assembly complexes, such as major and minor capsid proteins; while others, including the viral nuclear egress complex, the virus protein kinases pUS3 and pUL13, pUL21, pUL36, VP26, pUS9, and gE interact with host proteins to mediate other aspects of viral egress (5)(6)(7)(8)(9)(10)(11)(12)(13). Targeting these viral-host interactions for therapeutics may reduce development of drug resistance since the host partner is not subject to selective pressure (14).…”
Section: Introductionmentioning
confidence: 99%